Note on Relation between Bottom-Up Holographic Models and Large-Nc QCD - S. S. Afonin (Advances in High Energy Physics)
We discuss a derivation of the quadratic in fields part of action of bottom-up holographic models from some general properties of the large-Nc limit in QCD. The importance of rescaling of five-dimensional fields is emphasized using the soft wall model as an example.